Labor, Discipline, and the Underclass: Hierarchy in Orwell’s Down and Out in Paris and London - Donny Syofyan; Isramirawati Isramirawati (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
This study examines the construction of labor hierarchies and institutional discipline in George Orwell’s Down and Out in Paris and London. Using a qualitative textual analysis grounded in Marxist Literary Theory and New Historicism, the research investigates how social stratification is maintained within the service economy of 1930s Paris and the casual ward system of London. The primary analytical focus is two-fold: first, a deconstruction of the internal caste system of the modern hotel, where labor alienation and professional rivalries function to prevent proletarian solidarity; and second, an evaluation of the Vagrancy Act of 1824 as a state mechanism for social control through forced mobility.  Findings indicate that the hotel kitchen operates as a site of rigid stratification where the pride of the drudge creates a form of false consciousness among workers. Additionally, the study reveals that the state-mandated spike system in London functions to subdue the underclass by exhausting their intellectual and political capacity through purposeless movement. The research concludes that these institutions serve to manage a floating population through performative luxury and systemic de-pauperization, highlighting a profound waste of human potential in the pursuit of maintaining class boundaries.